Prone-Positioning for Severe Acute Respiratory Distress Syndrome Requiring Extracorporeal Membrane Oxygenation. Issue 2 (February 2022) - Petit, Matthieu; Fetita, Catalin; Gaudemer, Augustin; Treluyer, Ludovic; Lebreton, Guillaume; Franchineau, Guillaume; Hekimian, Guillaume; Chommeloux, Juliette; Pineton de Chambrun, Marc; Brechot, Nicolas; Luyt, Charles-Edouard; Combes, Alain; et al.
Abstract : OBJECTIVES: To determine the characteristics and outcomes of patients prone-positioned during extracorporeal membrane oxygenation for severe acute respiratory distress syndrome and lung CT pattern associated with improved respiratory system static compliance after that intervention. DESIGN: Retrospective, single-center study over 8 years. Settings: Twenty-six bed ICU in a tertiary center. MEASUREMENTS AND MAIN RESULTS: A propensity score–matched analysis compared patients with prone-positioning during extracorporeal membrane oxygenation and those without. An increase of the static compliance greater than or equal to 3 mL/cm H2 O after 16 hours of prone-positioning defined prone-positioning responders. The primary outcome was the time to successful extracorporeal membrane oxygenation weaning within 90 days of postextracorporeal membrane oxygenation start, with death as a competing risk. Among 298 venovenous extracorporeal membrane oxygenation–treated adults with severe acute respiratory distress syndrome, 64 were prone-positioning extracorporeal membrane oxygenation. Although both propensity score–matched groups had similar extracorporeal membrane oxygenation durations, prone-positioning extracorporeal membrane oxygenation patients' 90-day probability of being weaned-off extracorporeal membrane oxygenation and alive was higher (0.75 vs 0.54, p = 0.03; subdistribution hazard ratio [95% CI], 1.54 [1.05–2.58]) and 90-day mortality was lower (20% vs 42%, p < 0.01) than that for no prone-positioning extracorporeal membrane oxygenation patients. Extracorporeal membrane oxygenation–related complications were comparable for the two groups. Patients without improved static compliance had higher percentages of nonaerated or poorly aerated ventral and medial-ventral lung regions ( p = 0.047). CONCLUSIONS: Prone-positioning during venovenous extracorporeal membrane oxygenation was safe and effective and was associated with a higher probability of surviving and being weaned-off extracorporeal membrane oxygenation at 90 days. Patients with greater normally aerated lung tissue in the ventral and medial-ventral regions on quantitative lung CT-scan performed before prone-positioning are more likely to improve their static compliance after that procedure during extracorporeal membrane oxygenation. Abstract : Supplemental Digital Content is available in the text.